Converse nonimplication
In logic, converse nonimplication[1] is a logical connective which is the negation of converse implication (equivalently, the negation of the converse of implication).
Definition
Converse nonimplication is notated [math]\displaystyle{ P \nleftarrow Q }[/math], or [math]\displaystyle{ P \not \subset Q }[/math], and is logically equivalent to [math]\displaystyle{ \neg (P \leftarrow Q) }[/math] and [math]\displaystyle{ \neg P \wedge Q }[/math].
Truth table
The truth table of [math]\displaystyle{ P \nleftarrow Q }[/math].[2]
[math]\displaystyle{ P }[/math] | [math]\displaystyle{ Q }[/math] | [math]\displaystyle{ P \nleftarrow Q }[/math] |
True | True | False |
True | False | False |
False | True | True |
False | False | False |
Notation
Converse nonimplication is notated [math]\displaystyle{ p \nleftarrow q }[/math], which is the left arrow from converse implication ([math]\displaystyle{ \leftarrow }[/math]), negated with a stroke (/).
Alternatives include
- [math]\displaystyle{ p \not\subset q }[/math], which combines converse implication's [math]\displaystyle{ \subset }[/math], negated with a stroke (/).
- [math]\displaystyle{ p \tilde{\leftarrow} q }[/math], which combines converse implication's left arrow ([math]\displaystyle{ \leftarrow }[/math]) with negation's tilde ([math]\displaystyle{ \sim }[/math]).
- Mpq, in Bocheński notation
Properties
falsehood-preserving: The interpretation under which all variables are assigned a truth value of 'false' produces a truth value of 'false' as a result of converse nonimplication
Natural language
Grammatical
Example,
If it rains (P) then I get wet (Q), just because I am wet (Q) does not mean it is raining, in reality I went to a pool party with the co-ed staff, in my clothes (~P) and that is why I am facilitating this lecture in this state (Q).
Rhetorical
Q does not imply P.
Colloquial
Boolean algebra
Converse Nonimplication in a general Boolean algebra is defined as [math]\displaystyle{ q \nleftarrow p=q'p }[/math].
Example of a 2-element Boolean algebra: the 2 elements {0,1} with 0 as zero and 1 as unity element, operators [math]\displaystyle{ \sim }[/math] as complement operator, [math]\displaystyle{ \vee }[/math] as join operator and [math]\displaystyle{ \wedge }[/math] as meet operator, build the Boolean algebra of propositional logic.
|
and |
|
and |
|
then [math]\displaystyle{ \scriptstyle{y \nleftarrow x}\! }[/math] means |
| ||||||||||||||||||||||||||||||||||||||||||
(Negation) | (Inclusive or) | (And) | (Converse nonimplication) |
Example of a 4-element Boolean algebra: the 4 divisors {1,2,3,6} of 6 with 1 as zero and 6 as unity element, operators [math]\displaystyle{ \scriptstyle{ ^{c}}\! }[/math] (co-divisor of 6) as complement operator, [math]\displaystyle{ \scriptstyle{_\vee}\! }[/math] (least common multiple) as join operator and [math]\displaystyle{ \scriptstyle{_\wedge}\! }[/math] (greatest common divisor) as meet operator, build a Boolean algebra.
|
and |
|
and |
|
then [math]\displaystyle{ \scriptstyle{y \nleftarrow x}\! }[/math] means |
| ||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||
(Co-divisor 6) | (Least common multiple) | (Greatest common divisor) | (x's greatest divisor coprime with y) |
Properties
Non-associative
[math]\displaystyle{ r \nleftarrow (q \nleftarrow p) = (r \nleftarrow q) \nleftarrow p }[/math] if and only if [math]\displaystyle{ rp = 0 }[/math] #s5 (In a two-element Boolean algebra the latter condition is reduced to [math]\displaystyle{ r = 0 }[/math] or [math]\displaystyle{ p=0 }[/math]). Hence in a nontrivial Boolean algebra Converse Nonimplication is nonassociative. [math]\displaystyle{ \begin{align} (r \nleftarrow q) \nleftarrow p &= r'q \nleftarrow p & \text{(by definition)} \\ &= (r'q)'p & \text{(by definition)} \\ &= (r + q')p & \text{(De Morgan's laws)} \\ &= (r + r'q')p & \text{(Absorption law)} \\ &= rp + r'q'p \\ &= rp + r'(q \nleftarrow p) & \text{(by definition)} \\ &= rp + r \nleftarrow (q \nleftarrow p) & \text{(by definition)} \\ \end{align} }[/math]
Clearly, it is associative if and only if [math]\displaystyle{ rp=0 }[/math].
Non-commutative
- [math]\displaystyle{ q \nleftarrow p=p \nleftarrow q }[/math] if and only if [math]\displaystyle{ q = p }[/math] #s6. Hence Converse Nonimplication is noncommutative.
Neutral and absorbing elements
- 0 is a left neutral element ([math]\displaystyle{ 0 \nleftarrow p=p }[/math]) and a right absorbing element ([math]\displaystyle{ {p \nleftarrow 0=0} }[/math]).
- [math]\displaystyle{ 1 \nleftarrow p=0 }[/math], [math]\displaystyle{ p \nleftarrow 1=p' }[/math], and [math]\displaystyle{ p \nleftarrow p=0 }[/math].
- Implication [math]\displaystyle{ q \rightarrow p }[/math] is the dual of converse nonimplication [math]\displaystyle{ q \nleftarrow p }[/math] #s7.
Converse Nonimplication is noncommutative | ||||
---|---|---|---|---|
Step | Make use of | Resulting in | ||
s.1 | Definition | [math]\displaystyle{ \scriptstyle{q\tilde{\leftarrow}p=q'p\,}\! }[/math] | ||
s.2 | Definition | [math]\displaystyle{ \scriptstyle{p\tilde{\leftarrow}q=p'q\,}\! }[/math] | ||
s.3 | s.1 s.2 | [math]\displaystyle{ \scriptstyle{q\tilde{\leftarrow}p=p\tilde{\leftarrow}q\ \Leftrightarrow\ q'p=qp'\,}\! }[/math] | ||
s.4 | [math]\displaystyle{ \scriptstyle{q\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q.1\,}\! }[/math] | |
s.5 | s.4.right - expand Unit element | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q.(p+p')\,}\! }[/math] | |
s.6 | s.5.right - evaluate expression | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{qp+qp'\,}\! }[/math] | |
s.7 | s.4.left = s.6.right | [math]\displaystyle{ \scriptstyle{q=qp+qp'\,}\! }[/math] | ||
s.8 | [math]\displaystyle{ \scriptstyle{q'p=qp'\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{qp+qp'=qp+q'p\,}\! }[/math] | |
s.9 | s.8 - regroup common factors | [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q.(p+p')=(q+q').p\,}\! }[/math] | |
s.10 | s.9 - join of complements equals unity | [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q.1=1.p\,}\! }[/math] | |
s.11 | s.10.right - evaluate expression | [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q=p\,}\! }[/math] | |
s.12 | s.8 s.11 | [math]\displaystyle{ \scriptstyle{q'p=qp'\ \Rightarrow\ q=p\,}\! }[/math] | ||
s.13 | [math]\displaystyle{ \scriptstyle{q=p\ \Rightarrow\ q'p=qp'\,}\! }[/math] | |||
s.14 | s.12 s.13 | [math]\displaystyle{ \scriptstyle{q=p\ \Leftrightarrow\ q'p=qp'\,}\! }[/math] | ||
s.15 | s.3 s.14 | [math]\displaystyle{ \scriptstyle{q\tilde{\leftarrow}p=p\tilde{\leftarrow}q\ \Leftrightarrow\ q=p\,}\! }[/math] |
Implication is the dual of Converse Nonimplication | ||||
---|---|---|---|---|
Step | Make use of | Resulting in | ||
s.1 | Definition | [math]\displaystyle{ \scriptstyle{\operatorname{dual}(q\tilde{\leftarrow}p)\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{\operatorname{dual}(q'p)\,}\! }[/math] |
s.2 | s.1.right - .'s dual is + | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q'+p\,}\! }[/math] | |
s.3 | s.2.right - Involution complement | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{(q'+p)''\,}\! }[/math] | |
s.4 | s.3.right - De Morgan's laws applied once | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{(qp')'\,}\! }[/math] | |
s.5 | s.4.right - Commutative law | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{(p'q)'\,}\! }[/math] | |
s.6 | s.5.right | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{(p\tilde{\leftarrow}q)'\,}\! }[/math] | |
s.7 | s.6.right | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{p\leftarrow q\,}\! }[/math] | |
s.8 | s.7.right | [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] | [math]\displaystyle{ \scriptstyle{q\rightarrow p\,}\! }[/math] | |
s.9 | s.1.left = s.8.right | [math]\displaystyle{ \scriptstyle{\operatorname{dual}(q\tilde{\leftarrow}p)=q\rightarrow p\,}\! }[/math] |
Computer science
An example for converse nonimplication in computer science can be found when performing a right outer join on a set of tables from a database, if records not matching the join-condition from the "left" table are being excluded.[3]
References
- ↑ Lehtonen, Eero, and Poikonen, J.H.
- ↑ Knuth 2011, p. 49
- ↑ "A Visual Explanation of SQL Joins". 11 October 2007. http://www.codinghorror.com/blog/2007/10/a-visual-explanation-of-sql-joins.html.
- Knuth, Donald E. (2011). The Art of Computer Programming, Volume 4A: Combinatorial Algorithms, Part 1 (1st ed.). Addison-Wesley Professional. ISBN 978-0-201-03804-0.
External links
Original source: https://en.wikipedia.org/wiki/Converse nonimplication.
Read more |